Hardening of Concrete on Portland Cement During Heat Treatment (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
This article presents the results of experiments on the physical processes that occur during the hardening process of concrete in dry hot-climatic seasons and the reduction of their negative effects - as well as on the physical and mechanical properties.